LABOR PRODUCTIVITY IN PROJECT IMPLEMENTATION IN SAMPANG DISTRICT DURING TOBACCO PLANTATION SEASON - Agus Hendrianto; Hazin Mukti; Dedy Asmaroni; Fairus Zabadi (Journal Innovation of Civil Engineering (JICE), 2023)
Labor productivity is one of the main elements in determining the successful implementation of a construction project, one of the jobs that require a productive workforce is Fc' 25 Mpa Wiremesh Cement Concrete Pavement (M8). This research was conducted to know the level of productivity in Cement Concrete Pavement Fc' 25 Mpa Wiremesh and then compared with AHSP Bina Marga 2022 or Permen PUPR RI No. 1 of 2022 and mentions the solutions provided to the obstacles in the field during the implementation of M8 in the field. The results on the Karang Dalem – Patarongan Road Improvement project in Sampang District was 30.77 m3/OH for the foreman and 30.81 m3/ OH for workers, while the calculation of AHSP Bina Marga 2022 yields 20.75 m3/OH for foremen and 33.43 m3/OH for workers. In the Torjun – Pangarengan Road Improvement project in Torjun District, the calculations obtained results of 31.94 m3/OH for the foreman and 32.10 m3/OH for the workers, while the 2022 AHSP Bina Marga calculation obtained results of 20.75 m3/OH for the foreman and 37, 05 m3/OH for workers. Furthermore, the East Tobai – Poreh Road Improvement project in Sokobanah District was 20.32 m3/OH for foremen and 20.30 m3/OH for workers, while the 2022 AHSP Bina Marga calculations were 20.75 m3/OH for foremen and 32.27 m3/OH for workers. In general, the obstacles encountered in the implementation of the concrete road project in Sampang district during the tobacco growing season were the hot weather, labor motivation, and the distance of the casting supplier from the project work location. Keywords: Labor Productivity; Cement Concrete Pavement; Fc' 25 Mpa; Wiremesh (M8).